Pengaruh waktu dan jarak electroplating nikel pada baja karbon rendah terhadap kekerasan permukaan - S. Salman; I.M.A. Sayoga; I.D.K. Okariawan; S. Sinarep; R. Sutanto; A. Wiranata (Dinamika Teknik Mesin, 2019)
Electroplating is the process of coating an object with other metals that utilizes electricity in electrolyte liquid. In this research the carbon steel as anode material was coated by steel using nickel as catode.  The electroplating times and distances of anode catode were varied 6, 9, and 12 minutes and 150, 200, 250 mm. The hardness of the coated materal was evaluated later on by using micro vikers hardness testing. The result indicates that increasing the electroplating time rises the hardness values. The effect of the electroplating time on the harness is significant while the effect of the electrode distance is not.